Microbially-Enhanced Vanadium Mining and Bioremediation Under Micro- and Mars Gravity on the International Space Station - Cockell, Charles S.; Santomartino, Rosa; Finster, Kai; Waajen, Annemiek C.; Nicholson, Natasha; Loudon, Claire-Marie; Eades, Lorna J.; Moeller, Ralf; Rettberg, Petra; Fuchs, Felix M.; Van Houdt, Rob; Leys, Natalie; et al. (Frontiers in Microbiology, 2021)
As human explore and settle in space, they will need to mine elements to support industry. In preparation for the establishment of permanent human settlements across the Solar System, we conducted the ESA BioRock experiment on board the International Space Station to investigate whether biological mining could be accomplished under extraterrestrial gravity conditions. We tested the hypothesis that the gravity (g) level influenced the efficacy with which biomining could be accomplished from basalt, an abundant material on the Moon and Mars, under simulated Mars and Earth gravity, and microgravity, using three different microorganisms. One element of interest is mining interest is vanadium (V), which is added to steel to fabricate high strength, corrosion-resistant structural materials for buildings, transportation, tools and other applications. The results showed that Sphingomonas desiccabilis and Bacillus subtilis enhanced the leaching of vanadium under the three gravity conditions compared to sterile controls by 184.92 to 283.22 %. Gravity did not have a significant effect on mean leaching, thus showing the potential for biomining on Solar System objects with diverse gravitational conditions. Our results demonstrate the potential to use microorganisms to conduct elemental mining in the Solar System and other bioindustrial processes in locations with non-1 × g gravity such as asteroids, the Moon and Mars. These same principles apply to extraterrestrial bioremediation and elemental recycling beyond Earth.